Gerakan Literasi Budaya di Masyarakat : Penelitian - Muhammad Nawir; Fifi Arfiani; Nurul Mukhlisah; Nurul Amadyah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Cultural and civic literacy play a crucial role in shaping national character, strengthening national identity, and maintaining harmony within a diverse society. In today's era of globalization, local cultures are increasingly marginalized by the influence of foreign cultures, especially among younger generations. This paper explores the importance of cultural literacy in society, its roles and impacts on social life, and strategies to enhance it. Through a deep understanding of local values, norms, and wisdom, communities are expected to develop greater awareness of the need to preserve national culture. The discussion also highlights the importance of active participation from various societal elements—ranging from families and schools to community groups—in revitalizing cultural values through meaningful activities. Thus, the cultural literacy movement is not only a means of cultural preservation but also serves as a foundation for building an inclusive, tolerant society with a strong sense of national pride